IMPROVING THE DEVELOPMENT OF PEDAGOGICAL SKILLS IN FUTURE TEACHERS BASED ON PERSONALIZED TEACHING TECHNOLOGIES AS A PROBLEM - Homidova Dilrabo Tolibovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article outlines the content of personalized teaching technologies, using it to describe the pedagogical frameworks for the development of a student's personality in a technology lesson. Personalized education focuses on such issues as the intellectual and emotional-motivational development of students, the formation of knowledge and professional skills, the promotion of attitudes toward the educational process as a value, the development of activity, self-awareness and independence.